2002
DOI: 10.1091/mbc.e02-05-0285
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Type of cGMP Phosphodiesterase That Is Defective in the ChemotacticstmFMutants

Abstract: StmF mutants are chemotactic mutants that are defective in a cGMP phosphodiesterase (PDE) activity. We identified a novel gene, PdeD, that harbors two cyclic nucleotide-binding domains and a metallo-␤-lactamase homology domain. Similar to stmF mutants, pdeD-null mutants displayed extensively streaming aggregates, prolonged elevation of cGMP levels after chemotactic stimulation, and reduced cGMP-PDE activity. PdeD transcripts were lacking in stmF mutant NP377, indicating that this mutant carries a PdeD lesion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…A pdeD null mutant lacking the major cGMP-specific phosphodiesterase exhibits enhanced and prolonged cGMP responses like those of the stmF mutant (27). Yet in the early stages of differentiation (3 h) its Ca 2ϩ responses are reduced rather than enhanced, consistent with the early suggestion that cGMP acts to inhibit Ca 2ϩ influx (24).…”
supporting
confidence: 65%
“…A pdeD null mutant lacking the major cGMP-specific phosphodiesterase exhibits enhanced and prolonged cGMP responses like those of the stmF mutant (27). Yet in the early stages of differentiation (3 h) its Ca 2ϩ responses are reduced rather than enhanced, consistent with the early suggestion that cGMP acts to inhibit Ca 2ϩ influx (24).…”
supporting
confidence: 65%
“…Two candidate genes, PdeD (10) and PdeE, were identified. PdeE was assembled after several cycles of data base screening, yielding the complete coding sequence and 5Ј-untranslated region with at least 5-fold coverage.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding genes were named PdeD and PdeE by us (10) and GbpA and GbpB by others (11,13). Gene disruption and overexpression studies of PdeD/GbpA showed that the gene encodes the cGMP-stimulated cGMP phosphodiesterase, which is lacking in the chemotactic stmF mutants (10,13,14).…”
mentioning
confidence: 99%
“…This increased sensitivity was complemented by expression of SAPK␣ in these cells. Because cGMP can activate SAPK␣ kinase activity, we reinvestigated chemoattractant activation of SAPK␣ in cells lacking the cGMP phosphodiesterase (pdeD null cells) primarily responsible for degrading cGMP in response to cAMP stimulation (Meima et al, 2002). In this phosphodiesterase null mutation, cAMP-stimulated CGMP levels are highly elevated.…”
Section: Sapk␣ Is Activated By Stress and Required For Full Osmoprotementioning
confidence: 99%